2001
DOI: 10.1053/rapm.2001.24404
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for the treatment and prophylaxis of cluster headache

Abstract: Gabapentin was effective in the treatment of a patient with cluster headache. Further investigation of gabapentin compared with conventional treatments and placebo is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…50 In another case report, a 38-year-old man diagnosed with episodic cluster headache was effectively treated with gabapentin 300 mg bid. 51 The only side effect was initial drowsiness, which disappeared after 3 doses.…”
Section: Aeds For the Prevention Of Cluster Headache: Clinical Evidenmentioning
confidence: 98%
“…50 In another case report, a 38-year-old man diagnosed with episodic cluster headache was effectively treated with gabapentin 300 mg bid. 51 The only side effect was initial drowsiness, which disappeared after 3 doses.…”
Section: Aeds For the Prevention Of Cluster Headache: Clinical Evidenmentioning
confidence: 98%
“…Small open-label studies and case reports have indicated that the following drugs may be effective for cluster headache: methylphenidate, 134 baclofen, 135 tizanidine, 136 clonidine, 137 pizotifen, 138 chlorpromazine, 139 histamine, 140 leuprolide, 141 eletriptan, 142 and gabapentin. [143][144][145] The experience with these drugs and several others such as botulinum toxin, 146 cyproheptadine, diltiazem, and tamoxifen is too limited to support their routine use in the treatment of cluster headache. 147 Refractory Cluster Headache…”
Section: Othermentioning
confidence: 99%